Analisis Pengaruh Foreign Direct Invesment (FDI), Suku Bunga dan Nilai Tukar Rupiah Terhadap Expor Total Indonesia - Tulus Widjajanto; Sutrisno Sutrisno; Tri Anita (Universitas Indraprasta PGRI, 2020)
This study aims to find out the effect of foreign direct investment (FDI), interest rates, and exchange rates on Indonesia's total exports simultaneously and partially. FDI (Foreign Direct Investment) or foreign direct investment is one of the important characteristics of an increasingly global economic system. This begins when a company from one country invests in the long run into a company in another country. In this way companies in their home countries (commonly called 'home countries') can control companies that exist in investment destination countries (commonly called 'host countries') either in part or in full. The research method used is to use quantitative methods by analyzing secondary data using time series. The results of this study indicate that Foreign Direct Investment (FDI), interest rates, and exchange rates both simultaneously and partially affect the value of Indonesia's exports.